Adipose-derived stromal cell in regenerative medicine: A review - Tabatabaei Qomi, Reza (World J Stem Cells, 2017)
The application of appropriate cell origin for utilizing in regenerative medicine is the major issue. Various kinds of stem cells have been used for the tissue engineering and regenerative medicine. Such as, several stromal cells have been employed as treat option for regenerative medicine. For example, human bone marrow-derived stromal cells and adipose-derived stromal cells (ADSCs) are used in cell-based therapy. Data relating to the stem cell therapy and processes associated with ADSC has developed remarkably in the past 10 years. As medical options, both the stromal vascular and ADSC suggests good opportunity as marvelous cell-based therapeutics. The some biological features are the main factors that impact the regenerative activity of ADSCs, including the modulation of the cellular immune system properties and secretion of bioactive proteins such as cytokines, chemokines and growth factors, as well as their intrinsic anti-ulcer and anti-inflammatory potential. A variety of diseases have been treated by ADSCs, and it is not surprising that there has been great interest in the possibility that ADSCs might be used as therapeutic strategy to improve a wider range of diseases. This is especially important when it is remembered that routine therapeutic methods are not completely effective in treat of diseases. Here, it was discuss about applications of ADSC to colitis, liver failure, diabetes mellitus, multiple sclerosis, orthopaedic disorders, hair loss, fertility problems, and salivary gland damage.